Analytical investigation of the dynamics of a conceptual wave energy converter driven by vortex-induced vibrations (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Ocean wave energy represents a vast and underutilised source of renewable energy, offering immense potential to diversify and strengthen the offshore renewable energy mix. However, designing commercially viable wave energy converters (WECs) remains challenging. To address these limitations, this study explores integrating Vortex-Induced Vibration (VIV) with wave-induced motion in WECs to enhance energy capture efficiency.VIV, a phenomenon where fluid flow induces motions in structures, has demonstrated potential in wind and tidal energy applications but remains largely unexplored in wave energy systems. This research investigates the feasibility of combining VIV with WECs, identifying the necessary conditions for integration, including fluid-structure interactions and dynamic responses. Analytical models and simulations are presented in this paper ahead of preliminary experiments to evaluate the performance and practicality of this approach. Initial outputs highlight the potential for synergistic energy capture by leveraging wave-induced and VIV-driven motion.By addressing potential limitations associated with the combination of these two mechanisms, the research builds on and supports the future creation of a wave-induced prototype device.